Evaluation System on Haemodynamic Parameters for Stented Carotid Artery: Stent Pictorial Selection Method - Paisal, Muhammad Sufyan Amir; Taib, Ishkrizat; Ismail, Al Emran; Tajul Arifin, Ahmad Mubarak; Mahmod, Muhammad Faisal (International Journal of Integrated Engineering, 2019)
Stent implantation is an alternative invasive technique for treating the narrowed artery or stenosis in carotid artery to restore blood to the brain. However, the restenosis process is usually observed after a few weeks of carotid angioplasty and stenting due to abnormal progression of atherosclerosis and thrombosis. Many studies reported that the activity of atherosclerosis and thrombosis is majorly influenced by the geometrical strut configuration. Thus, this study was carried out to determine the haemodynamic performance on different geometrical stent strut configurations based on numerical modelling and statistical analyses. Six different stent strut configurations were 3-D modelled and simulated in different physiological conditions; normal blood pressure (NBP), pre-hypertension (PH) and hypertension stage one (HS1) through computational fluid dynamic (CFD) method. The haemodynamic performance of stent was analysed based on parameters namely time averaged wall shear stress (TAWSS), time averaged wall shear stress gradient (TAWSSG), oscillatory shear index (OSI), relative residence time (RRT) and flow separation parameter (FSP). Meanwhile, Pictorial Selection Method was used to evaluate the best haemodynamic stent performance based on a scoring system. From observation, stent Type II was seen to show the highest score for TAWSS, which was 3.44 regardless of any physiological conditions. For TAWSSG, the lowest score was observed for Type V stent with 0.36. Furthermore, Type VI stent displayed the highest score for OSI while Type IV has the lowest score for FSP with 3.09 and 1.23, respectively. On the other hand, RRT was seen varying according to the physiological condition where the highest score in NBP condition was achieved by Type I while PH and HS1 condition was achieved by Type VI. In conclusion, Type VI has the best stent performance, whereas Type IV has the worst stent performance regarding the scoring system based on haemodynamic parameters. Further, Type I, Type II, Type III and Type V stents showed moderate hemodynamic performances for all physiological conditions.